2014
DOI: 10.1007/s11524-014-9904-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regulation on Methadone and Buprenorphine Provision in the Wake of Hurricane Sandy

Abstract: Hurricane Sandy led to the closing of many major New York City public hospitals including their substance abuse clinics and methadone programs, and the displacement or relocation of thousands of opioid-dependent patients from treatment. The disaster provided a natural experiment that revealed the relative strengths and weaknesses of methadone treatment in comparison to physician office-based buprenorphine treatment for opioid dependence, two modalities of opioid maintenance with markedly different regulatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…This was seen as important for the health and wellbeing of clients, developing suitable emergency plans, and in considering issues around stock, dose verification, and scripting in a disaster context. These findings are consistent with previous research highlighting issues that have occurred following disasters in the USA [2,16,17,19,20], particularly around getting access to medication, verifying correct dosages, and obtaining scripts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was seen as important for the health and wellbeing of clients, developing suitable emergency plans, and in considering issues around stock, dose verification, and scripting in a disaster context. These findings are consistent with previous research highlighting issues that have occurred following disasters in the USA [2,16,17,19,20], particularly around getting access to medication, verifying correct dosages, and obtaining scripts.…”
Section: Discussionsupporting
confidence: 92%
“…Following Hurricane Sandy in New York in 2012, McClure and colleagues [17] found that clinics were unable to operate and were relocated. There were problems with communication with regulatory agencies as well as verification of dosages and client status.…”
Section: Introductionmentioning
confidence: 99%
“…7 Post Hurricane Sandy interviews were conducted with providers and administrators that offer pharmacological treatment for opioid use disorder using methadone and/or buprenorphine in public clinics and in community practices accepting Medicaid. 8 Methadone providers reported more barriers to continuity of care (i.e. poor communication with regulatory agencies, clinic relocation problems, lack of emergency preparedness strategies, and dosage and patient status verification difficulties) than buprenorphine providers (i.e.…”
mentioning
confidence: 99%
“…Drug dependence encounters also increased, which may be related to known loss of methadone treatment centers. 29 In addition, administrative encounters were also frequent, which we found almost universally to be visits for prescription refills, evidence of disruption of access to primary care. In each of these cases, the resulting effect was an increase in ED use, which reflects the need to anticipate and prepare for these disruptions.…”
Section: Discussionmentioning
confidence: 79%